Permainan Bahasa dalam Meda Sosial - Ary Setyadi (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2019)
The title of the article "In Social Media is" Language Games "(?)" Departing from the purpose of proof that the existence of Social Media is a source of data "language games". Such statements are reasonable, because the actors, adolescents or who youthful, can present the desired content of the message regardless of the rules of the binding language.The application of theory combines the linguistic theory of semantics with sociolinguistic (theory), because between them are empirical sciences. The existence of both of them complement each other. The assessment phase starts from: 1. provision of data, 2. classification and analysis of data, and 3. preparation / writing.The data finding is more secondary, because the data is obtained from written sources, that is, as the facts of the text in Social Media. The findings of the form of "language games" are based on: 1. text typology, and 2. text content (messages).The results of the study based on the typology of the text produce: a. type of word alignment (in sentence form), b. dialog type, and c. type of poetry. While the results of the study based on the contents (message) of the text produce: a. `satire ', b. `invitation ', c. `warning, and d. `harassment and / or punching`.